Bahasa English : Pengarauh Ajaran Hindhu dan Signifikasi Teologi Dalam Islam - Suroyo Suroyo; Bima Maulana Putra; Ni Luh Nyoman Seri Malini; Antonia Soriente; Robert Sibarani; Bedriati Ibrahim (Center for Research and Development of Religious Literature and Heritage, 2022)
The aim of this study is to examine the practice of Petang Megang tradition on indigenous Muslim Malay people in Pekanbaru Riau in welcoming the holy month of Ramadhan, and to investigate the influence of Hinduism on this annual tradition. Petang Megang ritual does not only function as a passed-on tradition, but also reflects the acculturation of Hindu and Islam, social interaction, and community culture. This research is a descriptive study, in which data obtained are presented, analyzed, and explained. This study found that Petang Megang tradition reflects a strong relationship between the two beliefs, Hindu and Islam. The relationship can be seen in the similar concepts of purification in Petang Megang which is similar to tirtayatra in Hindu and wudhu (ablution) in Islam. Despite bringing similarity to Hindu tradition, Petang Megang serves as a medium of Islamic dawah (propagation) where it introduces a cultural practice in its relation to religious event (Ramadan). This study suggests that Petang Megang is a symbol of longstanding harmonious co-existence between Hindu and Islam in the region.